Therapeutic potential of human umbilical cord mesenchymal stem cell-derived exosomes in myocardial infarction: from molecular mechanisms to clinical translation-an update - Ding, Nianhui; Zheng, Zaiyong; Zhang, Chunxiang (Frontiers in Pharmacology, 2025)
Myocardial infarction (MI) remains a leading cause of cardiovascular mortality despite advances in reperfusion strategies, necessitating innovative therapeutic approaches. Human umbilical cord mesenchymal stem cell-derived exosomes (HUCMSCs-Exos) have emerged as promising next-generation therapeutics, offering superior advantages including enhanced stability, reduced immunogenicity, and ability to cross biological barriers compared to cellular therapies. These naturally occurring nanovesicles exert comprehensive cardioprotective effects through multifaceted mechanisms encompassing anti-apoptotic signaling, angiogenesis promotion, immunomodulation, anti-fibrotic activity, oxidative stress reduction, and cardiac regeneration enhancement. The therapeutic arsenal includes diverse molecular cargo such as microRNAs (miR-29b, miR-133a-3p, miR-24-3p), long non-coding RNAs, circular RNAs, and bioactive proteins that synergistically target key pathophysiological processes in MI. Advanced engineering approaches, including genetic modification, surface functionalization, and biomaterial integration, have further enhanced therapeutic efficacy through targeted delivery and sustained release systems. While preclinical studies demonstrate significant cardioprotective effects, clinical translation faces challenges in standardization, manufacturing scalability, and regulatory approval. The convergence of innovative engineering strategies, personalized medicine approaches, and emerging technologies positions HUCMSCs-Exos as promising therapeutic approach that could fundamentally alter MI treatment paradigms and improve global cardiovascular health outcomes.